Land Use Effect on Milky Stork Habitat Selection in Matang Forest Reserve, Perak - Abd Rahman, Azimah; Mohd Nazri, Aimi Shahirah (Journal of Techno-Social, 2022)
The global Milky Stork population has undergone a rapid population decline with a current estimated population of 5500 individuals remaining worldwide. In Malaysia Milky Stork populations have declined more than 90% over the last 20 years and less than five individuals being observed recently in Pulau Kelumpang and Pulau Trong, the last known Milky Stork habitats in the Matang Forest Reserve. GIS application is used to analyse habitat selection of Milky Stork in study area. There are 16 different stations have been choosing in this research and three parameter has been set which is land use, vegetation and food availability. From the results, the highest density of Milky Stork that can be found is at Pulau Gula and the lowest density of Milky Stork is at Pulau Kelumpang which is only 1 individual was spotted. The result from this study also shows these birds are most likely to be found at disturbed area especially aquaculture activity. This aquaculture activity has provided them to an easy access towards food source. Research finding shown that since captive breeding birds program implemented by Department of wildlife and National Park (DWNP), they are most likely has lost their ability on foraging food in the wild. Some of the staff in DWNP Pulau Gula branch said that when it was rainy days, this bird will come to their building asking for food. The results also show that environment factor like vegetation, food and climate does not have any effects on density of Milky Stork. This situation is very contrary with previous studies that showing these birds are able to get their own food natural habitat.